A Case of Recalcitrant Plantar Warts Associated with Statin Use - Aaron G. Wernham; Shireen S. Velangi (Case Reports in Dermatological Medicine)
Background. Plantar warts are a common presenting skin complaint caused by the human papillomavirus. 1st line therapies include cryotherapy and topical salicylic acid. Where there is resistance to these treatments, consideration is made for 2nd line therapies, including intralesional bleomycin, imiquimod, 5-fluorouracil, and photodynamic therapy. We present a case of bilateral persistent plantar warts, resistant to treatment with repeated cryotherapy and topical salicylic acid over a 6-year period. Following a patient initiated decision to discontinue their statin medication, we observed rapid clearance of plantar warts without change to standard therapy or their environment. This case correlates with emerging literature demonstrating a link between statin medication and proliferation of HPV through increased levels of FOXP3+ regulatory T cells.